TANTANGAN E-COMMERCE DALAM TRANSFORMASI DIGITAL PADA UMKM DI INDONESIA - Hafiza (Talenta Publisher, 2023)
E-commerce transactions accounted for 8% of total retail sales in Indonesia in 2018 and are expected to increase to 18% by 2023, according to research conducted by Morgan Stanley, an American multinational investment bank. This is due to the changing behavior of customers, who are more prepared to pay more for greater convenience. This research is a literature review and the result of the researcher's thinking. The type of data used is secondary data with a qualitative approach. Broad market share, easier transactions, increased production, simpler payments, and more varied promotions are some of the benefits of digitalization for Indonesia's economic growth. Negative sides include the possibility of fraud and plagiarism, as well as a lack of labor absorption. In addition, the financial sector, agriculture, culture, tourism, and the creative economy are areas that can thrive in the digitalization era.